Acetamide‐modified hyper‐cross‐linked resin: Synthesis, characterization, and adsorption performance to phenol from aqueous solution. Issue 10 (30th October 2014) - Wang, Xiaomei; Patil, Prafulla D.; He, Chunlian; Huang, Jianhan; Liu, You‐Nian
ABSTRACT Acetamide‐modified hyper‐cross‐linked resin, HCP‐HMTA‐AA, was prepared and its adsorption performance was evaluated using phenol as the adsorbate. The prepared HCP–HMTA–AA owned predominant micro/mesopores and medium polarity, making it possess a superior adsorption to phenol as compared with polystyrene (PS), chloromethylated polystyrene (CMPS), hyper‐cross‐linked polymer (HCP) and amino‐modified hyper‐cross‐linked resin (HCP–HMTA). The adsorption enthalpy was −99.56 kJ/mol at zero fractional loading, multiple hydrogen bonding contributed to such a great adsorption enthalpy and an approximately planar hexahydric ring was formed between acetamide of HCP–HMTA–AA and phenol. The dynamic capacity of phenol on HCP–HMTA–AA was 291.3 mg/g at a feed concentration of 946.2 mg/L and a flow rate of 48 mL/h and the resin column was almost regenerated by a mixed solvent including 50% of ethanol (v/v) and 0.01 mol/L of sodium hydroxide (w/v). HCP–HMTA–AA was repeatedly used for five times and the equilibrium adsorption capacity for the five time reached 94.2% of the equilibrium adsorption capacity for the first time. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41597.